Development of compact and efficient volumetric apparatus for measuring absorption/desorption properties of hydrogen storage materials. (5th September 2022) - Zhu, Hongxing; Cheng, Honghui; Chen, Donglei; Ding, Zhi
Abstract: A compact volumetric apparatus has been developed for measuring hydrogen storage materials. In the ranges of 0–10 MPa and ambient temperature to 873 K, it can provide tests of Pressure-Composition-Temperature (PCT) isotherms, kinetics, and cycle life. All the tests can be efficiently and automatically completed without manual intervention. The components selection, principles and operations of the device were introduced in detail. At the same time, a novel calibration method for chamber volumes, which is automatically completed in two stages based on home-made LabVIEW programs, was developed. A Dynamic Volumes of Sample cell and Tube (DVST) method was proposed to overcome the influence of temperature gradient. A novel automatic dosing method with volume enlargement of reservoir was employed to improve the PCT testing efficiency of the setup. To improve the efficiency of cycle life measurements, a composite method including a Direct-Charge-Discharge (DCD) mode without any data recording was presented. In the end, the feasibility of the calibration method, data integrity and the robustness of the instrument were validated by La0·5 Ce0·5 Ni4 Co alloy. Similarly, the test efficiency of the equipment based on the automatic dosing method was verified by LaNi4·25 Al0.75 and La0·5 Ce0·5 Ni4 Co alloys. The results show that the data obtained by this apparatus is in good agreement with published dependable data. Graphical abstract: Image 1 Highlights: A compact volumetric setup for measuring hydrogen storage materials was developed. The setup can efficiently test PCT, kinetics and cycle life without intervention. A cost-effective and precise online volume calibration method was presented. A novel automatic PCT dosing method was proposed. A composite method is adopted to improve test efficiency of cycle life greatly.